Mental Health Help-Seeking in Parents and Trajectories of Depressive and Anxiety Symptoms: Lessons Learned From the Ontario Parent Survey During the COVID-19 Pandemic - Zhang, Xutong; Jambon, Marc; Afifi, Tracie O.; Atkinson, Leslie; Bennett, Teresa; Duku, Eric; Duncan, Laura; Joshi, Divya; Kimber, Melissa; MacMillan, Harriet L.; Gonzalez, Andrea (Frontiers in Psychology, 2022)
Tracking parents’ mental health symptoms and understanding barriers to seeking professional help are critical for determining policies and services to support families’ well-being. The COVID-19 pandemic has posed enormous challenge to parents’ mental health and the access to professional help, and there are important public health lessons that must be learned from the past two years’ experiences to inform future mental health responses to social- and family-level stressful events. This study examines the trajectories of parents’ depressive and anxiety symptoms over a year during the pandemic as related to their mental health help-seeking. Data were collected from a sample of parents residing in Ontario, Canada at baseline (May-June, 2020; Wave 1) and again one year later (Wave 2; referred to as W1 and W2 below). Parents (n = 2,439; Mage = 39.47, SD = 6.65; 95.0% females) reported their depressive and anxiety symptoms at both waves. Mental health help-seeking, including self-reported contact with professional help and perceived unmet mental health needs, was measured at W2. Parents were classified into four groups by mental health help-seeking. Inconsistent seekers and non-seeking needers, both reporting perceived unmet needs for professional help, showed greater increases in depressive and anxiety symptoms, whereas parents with no need or needs met showed smaller increases in depressive symptoms and decreases in anxiety symptoms. Belief in self-reliance and time constraints were the leading reasons for not seeking help. These findings suggest that over a year into the pandemic, parents with perceived unmet mental health needs were at greater risk for worsening depressive and anxiety symptoms. Recognizing the demands for mental health services when families experience chronic stressors and targeting the identified barriers may promote family well-being during and beyond this pandemic.